Examining the Decision Matrix between Dividends and Share Repurchases in Corporate Finance - Rahman, Abdul (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores the factors influencing a company's decision to choose between dividend payments and share repurchases and their impact on capital structure and shareholder value. Research Design and Methodology: The study identifies critical themes and trends shaping dividend and share repurchase decisions through a systematic review and analysis of existing literature, incorporating theoretical frameworks and empirical findings. The research methodology emphasizes rigor, transparency, and reflexivity, ensuring the credibility of the conclusions derived from the literature synthesis. Findings and Discussion: The results show that companies with stable cash flow choose dividends to provide consistent returns to shareholders. In contrast, companies with high growth prospects prefer share buybacks to maintain financial flexibility and increase EPS. Market conditions and investor preferences also play an essential role in this decision. Implications: This research provides insights for management to adjust the payout policy to market conditions and the company's strategic objectives to optimize shareholder value and maintain financial flexibility.